Anxiety and Adherence to Anti-Tuberculosis Treatment Among Tuberculosis Patients in Indonesia - Alihksan Agus; Muhammad Kurniawan; Rosmiati Rosmiati (CV. Global Health Publication, 2025)
Background: Tuberculosis (TB) is a major global public health problem requiring long-term adherence to anti-tuberculosis drug therapy to achieve treatment success and prevent drug resistance. Psychological factors, particularly anxiety, may negatively influence medication adherence and compromise TB treatment outcomes. This study aimed to determine the association between anxiety levels and adherence to anti-tuberculosis treatment among tuberculosis patients undergoing therapy at health care facilities. Methods: This quantitative analytical study employed a cross-sectional design involving 47 pulmonary TB patients undergoing treatment at health care facilities. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS), while medication adherence was assessed using a structured adherence questionnaire adapted from standard TB adherence indicators. Instrument validity was assessed through expert review, and reliability testing yielded a Cronbach’s alpha > 0.70. Data were analyzed using univariate analysis and the Chi-square test, with significance set at p < 0.05. Results: Most respondents demonstrated high adherence (61.7%), while 38.3% showed moderate adherence. The majority of patients were not anxious (66.0%), while 34.0% experienced mild anxiety. A statistically significant association was found between anxiety and medication adherence (p = 0.006), where patients with anxiety were more likely to have lower adherence (OR > 1). Conclusion: Anxiety is significantly associated with medication adherence among TB patients. Integrating mental health screening, patient education, and family support into TB programs is essential to improve adherence and treatment outcomes.